Physico-Chemistry and Organoleptic Fish Cake for Tuna (Thunnus albacores) Enriched with Eucheuma cottonii Seaweed - Notaria Alung; Albert Royke Reo; Grace Sanger; Engel Victor Pandey; Hanny Welly Mewengkang; Feny Mentang (Sam Ratulangi University, 2023)
One type of fish resource that has great potential in Indonesia is from large pelagic fish groups including tuna, tuna, and skipjack. Efforts to increase people's interest in consuming fish, with diversified products. The way that can be done to take advantage of fishery production is by diversifying fishery products and processing them into a variety of products. One of them is the abundance of tuna commodities in North Sulawesi, which has the potential to be developed into a product. This study aims to analyze the water content, fiber content, and organoleptic tests to obtain the product quality of tuna fish cake with the addition of Eucheuma cottonii seaweed. The data obtained from the results of the research conducted were calculated for the average value, then continued with the ANOVA test on SPSS and discussed descriptively. The results showed that the high water content value was obtained in treatment B2 with a water content value of 7.24 while the lowest value for treatments A1 and A2 was 3.06%. The highest crude fiber content was 0.2150 while the low fiber content was 0.057. Organoleptic results for fish cake products obtained panelists' preference level by looking at the results of taste, texture, aroma, and color values ​​in treatment B2 (frying fish cake) with the addition of 80% tuna and 20% seaweed. Keywords: Fish cake, Thunuus albacares, Eucheuma cottonii Abstrak Salah satu jenis sumber daya ikan yang memiliki potensi besar di Indonesia adalah dari kelompok ikan pelagis besar antaranya Tuna, Tongkol dan Cakalang. Upaya untuk meningkatkan daya minat masyarakat dalam mengkomsumsi ikan, dengan adanya produk diversifikasi. Cara yang dapat dilakukan untuk memanfaatkan produksi perikanan yaitu dengan cara diversifikasi produk hasil perikanan diolah menjadi beranekaragam. Salah satunya dengan jumlah komoditas ikan tuna yang melimpah di Sulawesi Utara berpotensi untuk dikembangkan menjadi sebuah produk. Penelitian ini bertujuan untuk menganalisis kadar air, kadar serat dan uji organoleptic untuk mendapatkan mutu produk fish cake ikan tuna dengan penambahan rumput laut Eucheuma cottonii. Data yang diperoleh dari hasil penelitian yang dilakukan dihitung nilai rata-ratanya, lalu dilanjutkan dengan uji ANOVA pada SPSS dan dibahas secara deskriptif. Hasil penelitian menunjukan bahwa nilai kadar air yang tinggi diperoleh pada perlakuan B2 dengan nilai kadar air sebesar 7.24 sedangkan perlakuan A1 dan A2 diperoleh nilai paling rendah sebesar 3.06%. Hasil kadar serat kasar yang paling tinggi adalah 0.2150 sedangkan nilai kadar serat yang rendah adalah sebesar 0.057. Hasil organoleptic untuk produk fish cake diperoleh tingkat kesukaan panelis dengan melihat hasil nilai rasa, tekstur, aroma dan warna pada perlakuan B2 (penggorengan fish cake) dengan penambahan ikan tuna 80% dan rumput laut 20%. Kata kunci: Fish cake, Thunuus albacares, Eucheuma cottonii